Recurrence prediction in chronic subdural hematomas: a risk stratification score based on 118 consecutive patients - Francesco M.C. Lioi; Jon Ramm-Pettersen; Andrea Fratini; Gabriele Dentato; Giovanni Facchinetti; Niccolo Colella; Luigi Rosito; Elena Furno; Camilla Riva; Andrea G. Ruggeri; Luca D'Angelo; Antonio Santoro; et al. (Brain and Spine)
Background: Chronic subdural hematoma (CSDH) is a frequent neurosurgical condition with a significant recurrence rate. Identifying patients at risk of recurrence is a topic of great interest to intercept this population in which to implement further therapeutic strategies. Objective: To develop and internally validate a risk-stratification score using preoperative radiological parameters to predict risk of CSDH recurrency. To establish a stratification approach based on easily available clinical and radiological variables. Methods: A retrospective analysis of 118 consecutive patients surgically treated for CSDH was conducted. Binary logistic regression was used to identify radiological preoperative predictors of recurrence, including Nakaguchi classification, cortical atrophy, and hematoma density. Results: A weighted scoring system has been developed and patients were stratified into three risk categories: low (0–2 points), moderate (3–5 points), and high (6–8 points). This grading system demonstrated a significant correlation with recurrence rates: 0 % in the low-risk group, 11.76 % in the moderate-risk group, and 25.71 % in the high-risk group. The model exhibited good discriminative ability in predicting the risk of CSDH recurrence. Conclusion: Hyperdense appearance, homogeneous or separated Nakaguchi-configuration and presence of cortical atrophy are predictive features of CSDH recurrence and can be incorporated into a score. The proposed grading system provides an effective preoperative tool for assessing CSDH recurrence risk, with a progressive increase in the recurrency rate between the three groups. This model enables personalized postoperative management, facilitating early identification of high-risk patients who may benefit from adjunctive treatments to reduce recurrence.